'It makes me feel alive': the socio-motivational impact of drama and theatre on marginalised young people. Issue 1 (2nd January 2017) - Hanrahan, Fidelma; Banerjee, Robin
ABSTRACT: An in-depth, longitudinal, idiographic study examined the impact of theatre and drama involvement on marginalised young people. Semi-structured interviews, at three separate time points over 2 years, were conducted with four young people (15–21 years of age) involved in a theatre project. Interpretative phenomenological analysis suggested that drama and theatre create space and support for the authentic self, and provide optimal conditions for promoting growth and resilience through voluntary engagement in a positive activity. In particular, the analysis highlighted the pivotal role of interpersonal relationships and a nurturing environment in re-engaging young people. Some participants' accounts also suggested that drama provides a uniquely engaging and therapeutic way to reflect on, express and explore experiences. The results are discussed in relation to core psychological processes underpinning self-development and key directions for further research.